Răspuns :
a+b+c supra 3 = 4,5 ,
a+b supra 2 = 3,5 => a+b =3,5 ori 2 , a + b = 7
si inlocuim in prima varianta
a+b+c supra 3 = 4,5
7+c supra 3 = 4,5
7+c = 4,5 ori 3
7+c = 13,5
c=13,5 - 7
c=6,5
a+b supra 2 = 3,5 => a+b =3,5 ori 2 , a + b = 7
si inlocuim in prima varianta
a+b+c supra 3 = 4,5
7+c supra 3 = 4,5
7+c = 4,5 ori 3
7+c = 13,5
c=13,5 - 7
c=6,5
(a+b+c)/3=4,5
a+b+c=4,5×3
a+b+c=13,5
(a+b)/2=3,5⇒ a+b=3,5×2=7 ⇒ a+b=7
inlocuim in a 2 a ecuatie si
7+c=13,5 ⇒ c=13,5-7⇒
c=6,5
a+b+c=4,5×3
a+b+c=13,5
(a+b)/2=3,5⇒ a+b=3,5×2=7 ⇒ a+b=7
inlocuim in a 2 a ecuatie si
7+c=13,5 ⇒ c=13,5-7⇒
c=6,5